Revitalizing Philippine unions prospects and constraints to social movement unionism - Aganon, Marie E. (Friedrich Ebert Stiftung and U.P. School of Labor and Industrial Relations, 2008)
"In this book, union revitalization is seen as a discourse and a strategy to arrest union decline and the crisis of unionism. Union revitalization and social movement unionism (as a strategy of union revitalization) address both strategic leverage and organizational capacity dimensions of union renewal. It requires serious and difficult analyses of union purpose, structures, processes and strategies and the necessary changes and adaptations required to sustain union revitalization in the long-term. The critical areas of focus and action are: (1) a broader articulation of trade union identity and purpose underpinned by class/populist/social movement type of unionism; (2) organizing; (3) membership involvement and activism; (4) union democracy; (5) opening up and forging alliances between unions and other social movements; and (6) labor internationalism."--Printer's description.